PENGARUH MODEL SEARCH, SOLVE, CREATE, AND SHARE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XII SMA NEGERI 1 KEPAHIANG - Annisa, Annisa (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical problem-solving ability is one of the most important ability to expand in mathematical learning. In fact, mathematical problem-solving ability is not yet optimal especially in grade 12 students of SMA Negeri 1 Kepahiang. One of the solution given is implement Search, Solve, Create, and Share learning model. The research’s aims are to analyze whether mathematical problem-solving ability of students that using SSCS learning model is better than the students that using direct learning and also to describe their ability who using SSCS model learning. The research methods are quasi-experiment and descriptive using Nonequivalent Posttest-Only Control Group design. Hypothesis is tested using Mann Whitney U test with result P-Value = 0,000 which means reject H0. The conclusion is mathematical problem-solving of students that using SSCS learning model is better than students that using direct learning in grade 12 of SMA Negeri 1 Kepahiang.Keywords — Mathematical Problem-Solving Ability, SSCS Learning Model, Direct Learning